Efficient Reverse Skyline Processing over Sliding Windows in Wireless Sensor Networks. (30th April 2015) - Min, Jun-Ki
Owning to the proliferation of cost-effective sensors, there has been an increased growth in a number of applications of wireless sensor networks (WSNs). In addition, the skyline operator as well as its variants such as the dynamic skyline and reverse skyline operator has attracted increasing attention since those are useful for multicriteria decision making applications. Since the energy efficiency is utmost important issue to prolong the network lifetime, in this paper, we proposed efficient algorithms to process a reverse skyline query over a sliding window in WSN environments. We first devise our algorithm for the data stream environments and extend it to WSN environments. To compute the reverse skyline, we partition the data space into several orthants with respect to a query point. And, in each orthant, we compute the reverse skyline independently using two buffers. In our experiment study, we demonstrate that our algorithm is much better than other algorithms.